2015
DOI: 10.1002/adma.201404531
|View full text |Cite
|
Sign up to set email alerts
|

Ferroelectricity and Antiferroelectricity of Doped Thin HfO2‐Based Films

Abstract: The recent progress in ferroelectricity and antiferroelectricity in HfO2-based thin films is reported. Most ferroelectric thin film research focuses on perovskite structure materials, such as Pb(Zr,Ti)O3, BaTiO3, and SrBi2Ta2O9, which are considered to be feasible candidate materials for non-volatile semiconductor memory devices. However, these conventional ferroelectrics suffer from various problems including poor Si-compatibility, environmental issues related to Pb, large physical thickness, low resistance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

37
677
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 877 publications
(746 citation statements)
references
References 115 publications
37
677
0
2
Order By: Relevance
“…After the observation of a remanent polarization and hysteresis in 10 nm thick films of 3 % Si doped HfO2 films 1 in a TiN-HfO2-TiN stack, the effect was additionaly found in Al-and Y-doped films 8,9 grown on TiN as well. More suitable dopants have been discovered since 10 . Furthermore, ferroelectricity was found in the 9 nm mixed oxide thin film Hf0.5Zr0.5O2 (HZO) 2 deposited on TiN electrodes, although neither the pure HfO2 nor the pure ZrO2 film exhibit ferroelectricity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After the observation of a remanent polarization and hysteresis in 10 nm thick films of 3 % Si doped HfO2 films 1 in a TiN-HfO2-TiN stack, the effect was additionaly found in Al-and Y-doped films 8,9 grown on TiN as well. More suitable dopants have been discovered since 10 . Furthermore, ferroelectricity was found in the 9 nm mixed oxide thin film Hf0.5Zr0.5O2 (HZO) 2 deposited on TiN electrodes, although neither the pure HfO2 nor the pure ZrO2 film exhibit ferroelectricity.…”
Section: Introductionmentioning
confidence: 99%
“…Müller 11 showed, that ZrO2 behaves antiferroelectric: above a critical field in the order of 1 MV/cm, a temperature dependent field induced phase transformation to the f-phase occurs. A recent review of the current status of HfO2, ZrO2 and HZO based ferroelectric films can be found in 10 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, hafnium dioxide (HfO 2 ) based insulators have emerged as the primary contenders to replace traditional SiO 2 in a variety of nano-electronic devices ranging from deep-scaled transistors to DRAM 1,2 and non-volatile memory cells. 3,4 Furthermore, thanks to the ferroelectricity property of both doped 5,6 and pure 7 HfO 2 , novel applications including memories 8 and high sub-threshold slope transistors 9 are envisioned. However, the reliability of the dielectric associated with electron trapping appears to be the "show stopper": It has already been shown that the positive bias-temperature instability (PBTI) limits the gate oxide scaling in metal-HfO 2 -Si transistors [10][11][12][13] while in flash cells, electron trapping in the intergate HfO 2 insulator degrades the program/erase window, retention, and endurance.…”
mentioning
confidence: 99%
“…However, precise identification of the phase(s) in these films is problematic due to experimental limitations such as the broadness of the thin-film diffraction spectra, unknown film texture and strain fields, and possible presence of multiple phases within a single film. Even the most conclusive phase determination to date [3], combining multiple characterization techniques, has had to rely on a pre-postulated set of possible structural candidates, which in turn has relied on a prior theoretical structure prediction study identifying possible metastable phases [15]. While the detailed investigation in Ref.…”
mentioning
confidence: 99%
“…This discovery is of great interest to the semiconductor industry and has led to intensive experimental [3][4][5][6][7][8][9][10][11][12][13][14] and theoretical [9,[15][16][17][18][19][20][21][22] research, because these materials are believed to avoid the problems typical for the traditional ferroelectric materials (such as lead zirconate titanate) during integration into microelectronic devices. However, precise identification of the phase(s) in these films is problematic due to experimental limitations such as the broadness of the thin-film diffraction spectra, unknown film texture and strain fields, and possible presence of multiple phases within a single film.…”
mentioning
confidence: 99%